HUBUNGAN PERILAKU KOMUNIKASI PETANI DENGAN KINERJA USAHATANI HIDROPONIK DI KOTA KENDARI - Iksul Iksul; Salahuddin Salahuddin; Megafirmawanti Lasinta (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
The expanding population and constrained agricultural land in Kendari City have catalysed the adoption of hydroponics as a solution for urban agriculture. Nevertheless, its efficacy remains suboptimal, underscoring the necessity for a study that explores the pivotal role of farmers' communication behaviour in facilitating innovation adoption and enhancing agricultural performance. The present study aims to analyse the relationship between farmers' communication behaviour and hydroponic farm performance. The research approach employs a quantitative method with a survey design. The population under scrutiny in this study consists of all hydroponic farmers in Kendari City, totalling 17 individuals. The data was collected through a census. The data collection techniques employed in this study encompassed various methods, including surveys, interviews, literature reviews, and documentation. The survey method was utilised as the primary technique for the collection of quantitative data from respondents via a structured questionnaire. The research variables were farmers' communication behaviour and hydroponic farming performance. The data analysis techniques employed in this study encompassed quantitative descriptive analysis and inferential analysis. The findings suggest that hydroponic farmers exhibit high levels of communication behaviour, particularly in terms of knowledge, intensity, and skills, which contribute significantly to farm performance categorised as "very good" in terms of quantity, quality, and timeliness. Correlation analysis indicates a positive and very strong relationship between communication behaviour and farm performance (ρ = 0.912; Sig. = 0.000), suggesting that an enhancement in farmers' communication behaviour is indicative of an optimal hydroponic farm performance. In the context of urban hydroponic agriculture, communication behaviour is no longer merely a supporting variable in the diffusion of innovation; rather, it is a primary determinant that integrates technical, managerial and market adaptation aspects to comprehensively enhance farm performance and sustainability.